Efectos contaminantes del uso y manejo de agroquimicos en la calidad del agua del estero Marañon del cantón Puebloviejo, plan de manejo ambiental, año 2012 - Bonilla Escobar, Edgar Geovanny. (2013)
Pollutants from agricultural activity and which are on the banks of aquatic systems are of interest and only a few countries are carried out in a systematic way, monitoring actions to control environmental shocking Monitoring the incidence of aquatic macroinvertebrates is an important tool in the evaluation process impacts on banks and any monitoring and control program, for monitoring living organisms provides a secure data conditions in their habitat located. This paper is an initiative to promote an effective methodology, easy and relatively inexpensive to monitor water quality. The research aims to determine the types of chemicals applied to crops that people Marañón Campus, evaluate the process of handling chemicals and pollution levels in the estuary Marañón, determine the water quality of the estuary Marañón by the presence of macroinvertebrates and develop a plan for environmental education on the use and handling of agrochemicals. As strategies for applied research work in the field, laboratory and documentary literature, the unit of analysis is the Marañón estuary. Understood monitoring as a quality management tool, the expected benefit, this paper achieved with the implementation of an environmental management plan, the same as in the near future to obtain a database collected at source analysis, in order to control water pollution, with the sole purpose of improving water quality and living in areas of influence.